The effects of dopamine receptor 1 and 2 agonists and antagonists on sexual and aggressive behaviors in male green anoles. - Alexandra N Smith; David Kabelik (PLoS ONE, 2017)
The propensity to exhibit social behaviors during interactions with same-sex and opposite-sex conspecifics is modulated by various neurotransmitters, including dopamine. Dopamine is a conserved neurotransmitter among vertebrates and dopaminergic receptors are also highly conserved among taxa. Activation of D1 and D2 dopamine receptor subtypes has been shown to modulate social behaviors, especially in mammalian and avian studies. However, the specific behavioral functions of these receptors vary across taxa. In reptiles there have been few studies examining the relationship between dopaminergic receptors and social behaviors. We therefore examined the effects of D1 and D2 agonists and antagonists on sexual and aggressive behaviors in the male green anole lizard (Anolis carolinensis). Treatment with high doses of both D1 and D2 agonists was found to impair both sexual and aggressive behaviors. However, the D1 agonist treatment was also found to impair motor function, suggesting that those effects were likely nonspecific. Lower doses of both agonists and antagonists failed to affect social behaviors. These findings provide some evidence for D2 receptor regulation of social behaviors, but in contrast with previous research, these effects are all inhibitory and no effects were found for manipulations of D1 receptors. A potential reason for the lack of more widespread effects on social behaviors using moderate or low drug doses is that systemic injection of drugs resulted in effects throughout the whole brain, thus affecting counteracting circuits which negated one another, making measurable changes in behavioral output difficult to detect. Future studies should administer drugs directly into brain regions known to regulate sexual and aggressive behaviors.